IMPLEMENTASI ASUHAN KEBIDANAN KOMPREHENSIF PADA MASA NEW NORMAL PANDEMI COVID-19 - Wigunantiningsih, Ana; Dewi Rosita, Siskana; Puspita Sari, Reni (Siklus : Journal Research Midwifery Politeknik Tegal, 2023)
The Maternal Mortality Rate (MMR) is the main indicator of the success of maternal health services. In addition to assessing maternal health programs, MMR is also an indicator to assess community health status. The MMR in Karanganyar Regency in 2021 was 19 cases (164.89/100,000 KH), a significant increase compared to the MMR in 2020 of 65.9/100,000 KH. The causes of maternal death included 15 cases (78.9%) due to COVID-19, 3 cases (15.8%) of bleeding, and 1 case (5.3%) due to pre-eclampsia. The purpose of this study was to identify the application of CoC, which consists of the frequency and accuracy of delivery of pregnancy care, identification of delivery care, postpartum and infant care, and family planning. This is a descriptive study using a mixed method approach (quantitative and qualitative). The population of this study was determined using a purposive sampling technique and consisted of mothers who had babies aged 30 days or older. Data collection uses a MCH book and checklist. The data obtained was processed through editing, coding, and scoring processes and analyzed using the Microsoft Excel application. The results of the study revealed that 60% of respondents had ANC according to schedule and regularly in the first, second, and third trimesters of pregnancy; 100% of respondents gave birth assisted by health workers with a screening examination first; 55% of respondents received KF and KN care at least three times according to schedule; and 25% of respondents have become family planning acceptors. Keywords: Implementation, Comprehensive Care, New Normal